Quality of Life of Patients with Anorexia and Bulimia Nervosa - Oliveira-Cardoso, Érika Arantes (2019)
This study aimed to evaluate the health-related quality of life (HRQoL) of patients with eating disorders (ED). The sample consisted of 40 predominantly young and adult female patients diagnosed with anorexia in outpatient treatment. A HRQoL instrument (SF-36) and the Eating Attitudes Test (EAT-26) were used. Results showed lowered HRQoL, especially in Mental Components. Impairments were observed in six of the eight domains evaluated regarding HRQoL of patients with higher scores on EAT-26, in five domains in patients with 22 years old or more, in General Health Perceptions (p = 0.02) and Mental Health domain (p = 0.03) in patients with less than five years of treatment and in Physical Functioning domain (p = 0.02) of patients with Bulimia Nervosa.